Reis em devoção, o Ticumbi de Conceição da Barra : ritual, memória e tradição - Nascimento, Aline Meireles do (2018)
Ticumbi is a cultural practice found in the north of the State of Espírito Santo, in the cities of Conceição da Barra and Itaúnas. This practice is a cultural heritage that has devotion to Saint Benedict and goes back to the time of the slavery. This work